Impact of BCR::ABL1 transcript type on RT-qPCR amplification performance and molecular response to therapy - Salmon, Matthew; White, Helen E; Zizkova, Hana; Gottschalk, Andrea; Motlova, Eliska; Cerveira, Nuno; Colomer, Dolors; Coriu, Daniel; Franke, Georg N; Gottardi, Enrico; Izzo, Barbara; Jurcek, Tomas; et al. (Leukemia, 2022)
Several studies have reported that chronic myeloid leukaemia (CML) patients expressing e14a2 BCR::ABL1 have a faster molecular response to therapy compared to patients expressing e13a2. To explore the reason for this difference we undertook a detailed technical comparison of the commonly used Europe Against Cancer (EAC) BCR::ABL1 reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) assay in European Treatment and Outcome Study (EUTOS) reference laboratories (n = 10). We found the amplification ratio of the e13a2 amplicon was 38% greater than e14a2 (p = 0.015), and the amplification efficiency was 2% greater (P = 0.17). This subtle difference led to measurable transcript-type dependent variation in estimates of residual disease which could be corrected by (i) taking the qPCR amplification efficiency into account, (ii) using alternative RT-qPCR approaches or (iii) droplet digital PCR (ddPCR), a technique which is relatively insensitive to differences in amplification kinetics. In CML patients, higher levels of BCR::ABL1/GUSB were identified at diagnosis for patients expressing e13a2 (n = 67) compared to e14a2 (n = 78) when analysed by RT-qPCR (P = 0.0005) but not ddPCR (P = 0.5). These data indicate that widely used RT-qPCR assays result in subtly different estimates of disease depending on BCR::ABL1 transcript type; these differences are small but may need to be considered for optimal patient management.
Keywords: Fusion Proteins, bcr-abl; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; chronická myeloidní leukemie; bcr-abl fúzní proteiny; Imatinib Mesylate; reziduální nádor; lidé; Humans; Neoplasm, Residual; Real-Time Polymerase Chain Reaction; kvantitativní polymerázová řetězová reakce; imatinib mesylát